Pengaruh Metode Diskusi Terhadap Hasil Belajar Pendidikan Agama Islam di Madrasah Aliyah Negeri 1 Tangerang - Guci, Alexander; Ripana, Anggi; Musthofa, Musthofa; Yulianti, Ade Dwi (LP. Ma'arif Janggan Magetan, 2024)
The discussion method is a way of presenting teaching materials with the teacher giving students or groups the opportunity to hold scientific discussions in order to gather opinions, make conclusions, or develop various alternative solutions to a problem. Meanwhile, learning outcomes are the value of student learning outcomes in Islamic religious education subjects. So in this research, in the field of Islamic religious education, the goal is to guide students to better know and understand the procedures related to changes in a Muslim, both in relation to God, humans and nature so that the objectives of learning can be achieved. This research is correlational research with two variables, namely the first variable X (discussion method) and variable Y (learning outcomes). The target population is all students at the MAN 1 Tangerang School, totaling 742. And the target population for class XI MAN 1 Tangerang is 117 students. The sample was taken using the Non Probability Quota technique, namely in class XI as many as 38 students. And researchers use product moment analysis. The results of calculations using the product moment correlation formula obtained a calculated r of 0.34, then the results were compared with the tabael r with a significance level of 5%, which was 0.32, meaning the calculated r was greater than the table r. Thus the null hypothesis which states that there is no significant positive influence between the discussion method on student learning outcomes in the field of Islamic religious education is rejected. Thus the research results conclude that there is a positive influence between the discussion method on student learning outcomes in the field of Islamic religious education studies in material on commendable morals and despicable morals at XI MAN 1 Tangerang.